DEVELOPMENT OF PROFESSIONAL SELF-EDUCATION COMPETENCE OF FUTURE SPECIALISTS WITH MEDICAL EDUCATION (Journal of Universal Science Research, 2023)
At the present stage of society development, the preparation of competitive specialists ready for professional growth and self-education should be considered an important task of education. Self-education is one of the priority directions in education and it is especially noticeable in the period of professional formation. It is obvious that professional training of future staff of medical specialists should not only provide a certain level of knowledge, skills and abilities, but also develop the ability to self-education.